BCR-ABL kinase domain mutations, including 2 novel mutations in imatinib resistant Malaysian chronic myeloid leukemia patients-Frequency and clinical outcome - Marjanu Hikmah Elias; Abdul Aziz Baba; Husin Azlan; Hassan Rosline; Goh Ai Sim; Menon Padmini; S. Abdul Wahid Fadilah; Ravindran Ankathil (Elsevier, 2024)
Discovery of imatinib mesylate (IM) as the targeted BCR-ABL protein tyrosine kinase inhibitor (TKI) has resulted in its use as the frontline therapy for chronic myeloid leukemia (CML) across the world. Although high response rates are observed in CML patients who receive IM treatment, a significant number of patients develop resistance to IM. Resistance to IM in patients has been associated with a heterogeneous array of mechanisms of which point mutations within the ABL tyrosine kinase domain (TKD) are the frequently documented. The types and frequencies of mutations reported in different population studies have shown wide variability. We screened 125 Malaysian CML patients on IM therapy who showed either TKI refractory or resistance to IM to investigate the frequency and pattern of BCR-ABL kinase domain mutations among Malaysian CML patients undergoing IM therapy and to determine the clinical significance. Mutational screening using denaturing high performance liquid chromatography (dHPLC) followed by DNA sequencing was performed on 125 IM resistant Malaysian CML patients. Mutations were detected in 28 patients (22.4%). Fifteen different types of mutations (T315I, E255K, G250E, M351T, F359C, G251E, Y253H, V289F, E355G, N368S, L387M, H369R, A397P, E355A, D276G), including 2 novel mutations were identified, with T315I as the predominant type of mutation. The data generated from clinical and molecular parameters studied were correlated with the survival of CML patients. Patients with Y253H, M351T and E355G TKD mutations showed poorer prognosis compared to those without mutation. Interestingly, when the prognostic impact of the observed mutations was compared inter-individually, E355G and Y253H mutations were associated with more adverse prognosis and shorter survival (P=0.025 and 0.005 respectively) than T315I mutation. Results suggest that apart from those mutations occurring in the three crucial regions (catalytic domain, P-loop and activation-loop), other rare mutations also may have high impact in the development of resistance and adverse prognosis. Presence of mutations in different regions of BCR-ABL TKD leads to different levels of resistance and early detection of emerging mutant clones may help in decision making for alternative treatment. Serial monitoring of BCR-ABL1 transcripts in CML patients allows appropriate selection of CML patients for BCR-ABL1 KD mutation analysis associated with acquired TKI resistance. Identification of these KD mutations is essential in order to direct alternative treatments in such CML patients.